2016
DOI: 10.18805/ijare.v50i4.11257
|View full text |Cite
|
Sign up to set email alerts
|

Growth pattern of millets in India

Abstract: The present study was carried out to estimate the growth rate of area, production and yield and to measure the contribution of different components to the growth rate of millets in India during the last six decades i.e. from 1950-51 to 2011-12. Area under sorghum, pearl millet, finger millet and total millets registered positive growth during 1950-51 to 1980-81 and negative growth subsequently. The production of total millets registered significant growth during overall study period due to increase in yield. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…The contributions of this crop to overall food grain production has reduced significantly from 22.17% to 6.94% between 1950-1951 and 2011-2012 [141,142]. Malathi, Appaji, Reddy, Dattatri and Sudhakar [142] studied the growth pattern of millets in India. The study concluded that there had been a significant decline in the area allotted for the cultivation of millets over the last few decades.…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of this crop to overall food grain production has reduced significantly from 22.17% to 6.94% between 1950-1951 and 2011-2012 [141,142]. Malathi, Appaji, Reddy, Dattatri and Sudhakar [142] studied the growth pattern of millets in India. The study concluded that there had been a significant decline in the area allotted for the cultivation of millets over the last few decades.…”
Section: Discussionmentioning
confidence: 99%
“…Finger millet is the richest in calcium content, about 10 times that of rice or wheat. In this fashion, nutrient to nutrient, every single millet is extraordinarily superior to rice and wheat and therefore is the solution for the malnutrition that affects a vast majority of the Indian population (Malathi et al, 2016).…”
Section: Mineralsmentioning
confidence: 99%
“…India is the world's largest producer of millets. In India, millets are cultivated in an area of 15.48 million hectares producing 17.2 million tonnes with a yield of 1111 kg/ha [4].…”
Section: Introductionmentioning
confidence: 99%